Helicobacter pylori and cagA gene detected by polymerase chain reaction in gastric biopsies: correlation with histological findings, proliferation and apoptosis - Leite, Katia Ramos Moreira (2005)
CONTEXT Al',O OBJECTIVE: lhe virulence oi Helicobacter pylori (HP) in gastroduodenal disease is related to pathogenicity islands (cagPAI) present in some strains. lnfection with cagPAI induces IL-8 secretion, increases epithel ial cell prolileration and may be important in carcinogenesis. Our objective was to detect HP and the cagA gene (cagPAI marker) by polymerase chain reaction (PCR) and to correlate these results to histological lindings, epithelial cell prolileration and apoptosis. DESIGN AND SETTING: Retrospective, ai lhe Surgical and Molecular Pathology Laboratory, Hospital Sírio-Libanês. METHODS: DNA samples isolated lrom 164 gastric biopsies were used for HP detection by PCR. cagl'AI+ was identilied in HP+ cases by cagA gene amplilication. AII cases were submitted to immunohistochemistry to evaluate cell prolileration, and lUNEL to detect apoptosis. Statistical analysis was perlormed to compare results. RESULTS: HP was detected in 67.7% oi the patients, with good correlation between HP inlection and moderate to severe gastritis, gastric ulcer and MALl lymphoma. lhere was a correlation between cagPAI+ strains and severa gastric diseases including cancer. lhe risk oi gastric ulcer, adenocarcinoma and MAll lymphoma was 8.8 times higher for cagl'AI+ patients. cagPAI+ inlection was related to higher prolileration rates. lhe prolileration/apoptosis index was signilicantly h igher for cagPAI+ patients. CONCLUSION: Cell growth deregulation in cagPAI+ patients could be demonstrated by lhe difference in the prolileration index. We believe that this explains the carcinogenic role oi Helicobacter pylori.